2009
DOI: 10.1016/j.ijcard.2008.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in α-adrenergic receptor-mediated vascular tone contributes to improved arterial compliance with endurance training

Abstract: Background-Regular aerobic exercise improves large artery compliance in middle-aged and older humans. However, the underlying mechanisms are unknown. We tested the hypothesis that the improved central arterial compliance with endurance training is mediated by decreased α-adrenergic tone and/or increased endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 34 publications
(39 reference statements)
0
27
0
Order By: Relevance
“…Of these structural changes, it has been theorized that non-enzymatic glycation would be the most responsive to aerobic exercise, through pulsatile stretching and breaking of collagen crosslinks. 30 Breaking down of the diabetes-associated collagen crosslinks, as well as short-term aerobic training-induced improvements in sympathetic tone 32 and increase in nitric-oxide induced vasodilatory activity 33 could all potentially explain the short-term reductions in arterial stiffness seen in this study. The fact that we were unable to demonstrate any training-induced improvements in fasting blood glucose, blood pressure and lipid levels might be one explanation for the training-resistant nature of arterial stiffness in our high-risk subjects over the longer term.…”
Section: Discussionmentioning
confidence: 88%
“…Of these structural changes, it has been theorized that non-enzymatic glycation would be the most responsive to aerobic exercise, through pulsatile stretching and breaking of collagen crosslinks. 30 Breaking down of the diabetes-associated collagen crosslinks, as well as short-term aerobic training-induced improvements in sympathetic tone 32 and increase in nitric-oxide induced vasodilatory activity 33 could all potentially explain the short-term reductions in arterial stiffness seen in this study. The fact that we were unable to demonstrate any training-induced improvements in fasting blood glucose, blood pressure and lipid levels might be one explanation for the training-resistant nature of arterial stiffness in our high-risk subjects over the longer term.…”
Section: Discussionmentioning
confidence: 88%
“…However, analogous assessments are experimentally challenging in humans, and future studies are needed to examine the contribution of any structural changes to reduced arterial stiffness with exercise in humans. In addition, exercise may also induce functional changes to the vasculature via mechanisms other than reduced NFkB signalling, such as alterations in the sympathetic nervous system [27], TNF-α [28], endothelin-1 [29] signalling or the COX 1/2 pathway [30]. …”
Section: Discussionmentioning
confidence: 99%
“…In this review, only two studies measured PWV, specifically baPWV, and both showed significant reductions after 12 weeks of exercise intervention [23,37]. The exercise-induced reduction of arterial stiffness may be mediated by a decrease of α-adrenergic receptor tone in arterial smooth muscle cells; thus, increasing arterial elasticity [38]. Maeda www.bjbms.org vascular tone leads to better arterial compliance [39].…”
Section: Resultsmentioning
confidence: 99%